Affective Immunology: The Crosstalk Between Microglia and Astrocytes Plays Key Role? - Yang, Linglin; Zhou, Yunxiang; Jia, Honglei; Qi, Yadong; Tu, Sheng; Shao, Anwen (Frontiers in Immunology, 2020)
Emerging evidence demonstrates the critical role of the immune response in the mechanisms relating to mood disorders, such as major depression (MDD) and bipolar disorder (BD). This has cast a spotlight on a specialized branch committing to the research of dynamics of the fine interaction between the emotion (or affection) and immune response, which has been termed as ‘affective immunology’. Inflammatory cytokines and gut microbiota are actively involved in affective immunology. Furthermore, abnormalities of the astrocytes and microglia have been observed in mood disorders from both postmortem and molecular imaging studies, however, the underlying mechanisms remain elusive. Notably, the crosstalk between astrocyte and microglia acts as a mutual and pivotal intermediary factor modulating the immune response posed by inflammatory cytokines and gut microbiota. In this study, we propose the ‘alterd astrocyte-microglia crosstalk (AAMC)’ hypothesis which suggests that the astrocyte-microglia crosstalk regulates emotional alteration through mediating immune response and thus, contributing to the development of mood disorders.